A single-cell transcriptome atlas of the aging human and macaque retina. Issue 4 (25th August 2020) - Yi, Wenyang; Lu, Yufeng; Zhong, Suijuan; Zhang, Mei; Sun, Le; Dong, Hao; Wang, Mengdi; Wei, Min; Xie, Haohuan; Qu, Hongqiang; Peng, Rongmei; Hong, Jing; et al.
ABSTRACT: The human retina is a complex neural tissue that detects light and sends visual information to the brain. However, the molecular and cellular processes that underlie aging primate retina remain unclear. Here, we provide a comprehensive transcriptomic atlas based on 119 520 single cells of the foveal and peripheral retina of humans and macaques covering different ages. The molecular features of retinal cells differed between the two species, suggesting distinct regional and species specializations of the human and macaque retinae. In addition, human retinal aging occurred in a region- and cell-type-specific manner. Aging of human retina exhibited a foveal to peripheral gradient. MYO9A − rods and a horizontal cell subtype were greatly reduced in aging retina, indicating their vulnerability to aging. Moreover, we generated a dataset showing the cell-type- and region-specific gene expression associated with 55 types of human retinal disease, which provides a foundation to understanding of the molecular and cellular mechanisms underlying human retinal diseases. Such datasets are valuable to understanding of the molecular characteristics of primate retina, as well as molecular regulation of aging progression and related diseases.